Decolonization and the French of Algeria Bringing the Settler Colony Home - Choi, Sung-Eun.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
In 1962, almost one million people were evacuated from Algeria. France called these citizens Repatriates to hide their French Algerian origins and to integrate them into society. This book is about Repatriation and how it became central to France's postcolonial understanding of decolonization, the Algerian past, and French identity.
Keywords: History; History, Modern; Africa -- History; Africa, North -- History; France -- History; Imperialism; International relations; History; History of France; Imperialism and Colonialism; African History; History of North Africa; International Relations; Modern History; Electronic books